The Relationship of Th1/Th2 Cytokine Polarization at Parturition in Cows and SOCS3 Level With Some Postpartum Diseases - Oznur Yilmaz Koc; Ali Risvanli (Veterinary Medicine and Science)
ABSTRACT Th1/Th2 polarisation and suppressor of cytokine signalling‐3 (SOCS3) are important indicators of the humoral and cellular immune system activity in cows. The aim of this study was to determine the correlation of postpartum diseases with the levels of Th1/Th2 polarisation and SOCS3 at the time of parturition. The study examined 180 cows (90 with normal parturition [NP] and 90 with dystocia [D]). Blood samples were taken from the cows once at the time of calving. Two subgroups were created among cows with NP: those without the postpartum disease (NP [−], n = 45) and those with postpartum disease (NP [+], n = 45). Likewise, two subgroups were created among D cows: those without postpartum disease (D [−], n = 45) and those with postpartum disease (D [+], n = 45). Cytokine analyses were performed using species‐specific commercial ELISA kits. In the NP (−) group, it was found that Th1/Th2 cytokine polarisation was in the Th1 direction due to the increase in the concentration of IFN‐γ, TNF‐α and IL‐2 in four subgroups grouping with different types of parturition and diseases. It was concluded that it would be appropriate to strengthen cellular immunity. In cases of postpartum diseases, Th1/Th2 polarisation shifted towards Th2 due to the increase in IL‐4 and IL‐5 concentrations in cows that performed NP and developed mastitis in the postpartum period. These results suggest that it would be beneficial to support the Th2 aspect (i.e. humoral immunity) in cows that have undergone NP and develop mastitis in the postpartum period.